2022
DOI: 10.1086/714777
|View full text |Cite
|
Sign up to set email alerts
|

Improved Multilevel Regression with Poststratification through Machine Learning (autoMrP)

Abstract: Multilevel regression with post-stratification (MrP) has quickly become the gold standard for small area estimation. While the first MrP models did not include contextlevel information, current applications almost always make use of such data. When using MrP, researchers are faced with three problems: how to select features, how to specify the functional form, and how to regularize the model parameters. These problems are especially important with regard to features included at the context level. We propose a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…Besides using a classical multilevel regression model, we also consider four machine learning classifiers: principle components analysis, lasso regression, gradient tree boosting, and a support vector machine. Recent research has shown that this ensemble method can increase the accuracy of MRP methods by up to 20% [20]. The multi-level modelling and poststratification analysis was executed with the R package autoMrP on a high-performance computer using 128 processor cores.…”
Section: Local Area Estimationmentioning
confidence: 99%
“…Besides using a classical multilevel regression model, we also consider four machine learning classifiers: principle components analysis, lasso regression, gradient tree boosting, and a support vector machine. Recent research has shown that this ensemble method can increase the accuracy of MRP methods by up to 20% [20]. The multi-level modelling and poststratification analysis was executed with the R package autoMrP on a high-performance computer using 128 processor cores.…”
Section: Local Area Estimationmentioning
confidence: 99%
“…principle components analysis (PCA), lasso regression, gradient tree boosting, and a support vector machine. Recent research has shown that this ensemble method can increase the accuracy of MrP methods by up to 20% 30 . The multi-level modelling and post-stratification analysis was executed with the R package autoMrP on a cluster using 128 cores.…”
Section: Local Area Estimationmentioning
confidence: 99%
“…This approach allows the estimation of state-level public opinion from national surveys (Gelman and Little 1997;Lax and Phillips 2009;Pacheco 2014). To estimate the MRP models and the uncertainty around the resulting estimates, we use the R-package "autoMrP" (Broniecki, Leemann, and Wüest 2021). 5 Stimson's Dyad Ratios Algorithm can be downloaded here: http://stimson.web.unc.edu/software/.…”
Section: Introductionmentioning
confidence: 99%
“…9 The relationship between our measure and Stimson's mood exceeds comparable correlations between the BRFH measure and Stimson's mood, offering further validation to our approach. 10 To gain a further sense of the new estimates, we return to the analysis of southern states and examine the relationship between annual changes in the new measure and 8 Of course, uncertainty exists around these estimates (As noted above, we use the R-package "autoMrP" [Broniecki, Leemann, and Wüest 2021] to estimate this uncertainty). Our measures are based on the percent offering a liberal response, while Stimson's estimates are based on the percent offering a liberal response out of those who offered a liberal or conservative response (i.e., middle categories are omitted from the denominator).…”
mentioning
confidence: 99%